Low-Mills family papers - Hillard, Harriet Low, 1809-1877.; Loines, Mary Hillard, 1844-1944.; Low, Abiel Abbot, 1811-1893.; Low, Edward Allen, 1817-1898.
Correspondence, diaries, journals, commonplace books, scrapbooks, financial records, genealogical material, photographs, printed material, and other papers concerning the activities of the Low (Lowe), Mills, Hillard (Hellard), and Loines families from approximately 1800 to 1950. Documents the family's business in the China trade based in Salem, Mass., and after 1829, Brooklyn, N.Y., primarily working with Russell and Company, Canton, China; social attitudes, cultural tastes, religious views, and economic conditions of 19th century America; and travel in China, Europe, and the Middle East during the 19th century. Subjects include the presidential administration of Abraham Lincoln, the Civil War, Confederate and Union navies, African American history, National Freedmen's Relief Association, G.P. Putnam & Son, and Americans living in China.
Includes a transcript of the journal kept by Harriet Low Hillard concerning her stay in Macau, 1829-1834, prepared by Arthur William Hummel; correspondence of family friend, George Haven Putnam, during his Civil War service with the 175th New York Volunteers; memoir of Mary Hillard Loines describing her involvement in the suffrage movement and her correspondence regarding the convention of the American Women's Suffrage Association in 1869; papers of Russell Hillard Loines concerning the poets Rupert Brooke, Walter De la Mare, and Robin Lampson; papers of the Mary Hillard Loines family; and a letter from Franklin D. Roosevelt concerning the candidacy of Alfred Emanuel Smith.
Microfilm edition of Harriet Low's journal, volume 6, available
Microfilm edition of the typescript of Harriet Low's journal, 1829-1834, edited and annotated by Arthur W. Hummel, available
Microfilm produced from original and typescript in the Manuscript Division.
In part, positive photocopies and typewritten transcripts.
Library of Congress Prints and Photographs Division.
Prominent family engaged in China trade.
Keywords: Brooke, Rupert, -- 1887-1915 -- Poetry; De la Mare, Walter, -- 1873-1956 -- Poetry; Hummel, Arthur W. -- 1884-1975.; Lincoln, Abraham, -- 1809-1865.; Lampson, Robin, -- 1900- -- Poetry; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Smith, Alfred Emanuel, -- 1873-1944.; Hellard family; Loines family; Lowe family; Mills family; Confederate States of America. -- Navy; United States. -- Army. -- New York Infantry Regiment, 175th (1862-1865); United States. -- Navy; American Women's Suffrage Association; G.P. Putnam & Son; National Freedman's Relief Association; Russell & Company (Guangzhou, China); African Americans -- History; Americans -- China; Freedmen -- United States; Publishers and publishing -- United States; Suffrage -- United States; Brooklyn (New York, N.Y.) -- Commerce; China -- Commerce -- United States; China -- Description and travel; Europe -- Description and travel; Macau (China); Middle East -- Description and travel; Salem (Mass.) -- Commerce; United States -- Commerce -- China; United States -- Economic conditions -- 19th century; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- Politics and government -- 1861-1865.; United States -- Religious life and customs; United States -- Social life and customs -- 19th century